38.7k views
5 votes
-6x-3y=3,-6x+7y=-7

I would really appreciate whoever could help me answer this equation I don't get the process.

1 Answer

2 votes
Let's solve this system thru the elimination method:

-6x-3y=3 Mult. all terms by -1 to obtain 6x+3y = -3
-6x+7y=-7 Add your result to the second equation:

6x+3y = -3
-6x+7y=-7
----------------
10y = -10, and so y = -1. Subst. -1 for y in the first equation and then solve the result for x. You'll find that x = 0.

Thus, the solution is (0, -1).
User Dfang
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.